PENGARUH SUKU BUNGA KEDIT KONSUMSI, PENDAPATAN DAN INFLASI TERHADAP PERMINTAAN KREDIT KONSUMSI PADA BANK PERKREDITAN RAKYAT DI PROVINSI RIAU TAHUN 2008-2019 - Wa, Ratnasari Dessy; Any, Widayatsari; Hendro, Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to determine the effect of interest rate of consumption credit, income and inflation to consumption credit demand on Rural Banks in Riau Province. The method used is descriptive quantitative and analyzed simultaneously and partially with OLS (ordinary least square) multiple linear regression. The result of this study shows simultaneously variable of interest rate of consumption credit, income and inflation give significant effect to consumption credit demand on Rural Banks in Riau Province. Partially, interest rate of consumption has negative and significant on consumption credit, income has positive and significant on consumption credit, however inflation has negative and insignificant on consumption credit. Value of determination coefficient shows that interest rate of consumption credit, income and inflation has effect to the consumption credit demand to 75,46% and the remaining 24,54% in effected by other factors outside this research.Keywords: Interest Rate of Consumption Credit, Income, Inflation, Credit of Consumption